Significance of the differential growth, relative tissue shifts and the vascular bed in limb development - Seichert, V (Acta Universitatis Carolinae. Medica. Monographia, 1988)
1. A method for planimetric measurement of areas of standardized dorsoventral projections of embryonal limbs was elaborated. The method permits a quantitative study of the growth of embryonic limbs at early stages of development, since the stage of flat limb bud until the stage at which the external shape of the limb (bending in joint regions and increase in volume) interferes with the simplification of its three-dimensional characteristics to two-dimensional ones of its dorsoventral projection. (Until stage 31-32HH for the chick embryo, see fig. 1 and 2). 2. A method of linear marking was elaborated (fig. 3). The marker proper are India-ink particles suspended in gelatin. Such stained gelatin is spread over a glass carrier (a glass fibre 10-20 microns thick) in the form of a thin film. After drying the fibre is cut in rods of a length desired for the appropriate linear mark. The marks can be introduced into the tissue by a single stab. After the gelatin film had swollen owing to the presence of tissue fluids, it is detached from the carrier surface and the carrier can be removed from the tissue. After the gelatin had been resorbed, a linear mark remains in the tissue. Deformations of the mark line and the scattering of India-ink particles which actually form the mark facilitates the assessment of the growth pattern of the respective marked tissue (see fig. 4-6). 3. During our studies of the differential growth of the wing bud with the method of linear marking the newly coined term "relative tissue shift" had to be specified. That term has been used for designating changes of the mutual position of tissue areas which could not be defined exactly as to their topography within a region or organ (such as the wing bud), showing fluent transitions between one another. If areas with different growth activities occur in the region studied, such areas undergo an uneven increase (differential growth). Thus another factor is added to those operating in the growth process, namely the direction of expansion of the different growing areas of the region studied to one another. The resultant of the mutual ratios of the voluminal growth of the neighbouring tissue areas and the directions of their expansion are the relative tissue shifts in the sense used in our studies.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: teratogeny; Wings, Animal; citráty; kyselina citronová; Mesoderm; končetiny; Extremities; Adenine; Morphogenesis; Citrates; adenin; křídla zvířecí; Teratogens; Citric Acid; abnormality vyvolané léky; Ectoderm; daktinomycin; ektoderm; Dactinomycin; Animals; kuřecí embryo; Abnormalities, Drug-Induced; zvířata; mezoderm; Chick Embryo; morfogeneze